TOURISM MARKETING COMMUNICATION STRATEGIES FOR POSITIONING GOSONG TELAGA BEACH IN ACEH SINGKIL AS A LEADING TOURIST DESTINATION - Jahirun Manik (Program Pascasarjana UIN Sumatera Utara, 2026)
Gosong Telaga Beach, located in Aceh Singkil Regency, is a marine tourism destination with considerable potential to be developed as a leading regional tourist destination. Its natural attractions, including coastal scenery, expansive sandy shores, and a relatively pristine coastal environment, constitute its primary appeal to visitors. However, this potential has not been fully supported by an effective marketing communication strategy, resulting in limited exposure and destination competitiveness compared with other tourist destinations. This study aims to analyze the marketing communication strategies employed to promote Gosong Telaga Beach as a leading tourist destination and to identify the factors that hinder their implementation. The study adopts a qualitative approach using a descriptive method. Data are collected through observation, in-depth interviews, and documentation involving representatives of the Aceh Singkil Regency Tourism Office, destination managers, local communities, tourism business operators, and tourists as research informants. Data are analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings are expected to demonstrate that the marketing communication strategies implemented include the use of social media, digital promotion, word-of-mouth marketing, the publication of tourism activities, and collaboration with various stakeholders to enhance the destination’s image and attractiveness. The study also identifies several obstacles, including limited promotional budgets, inadequate supporting facilities, low levels of community participation, limited human resource capacity, and competition from other tourist destinations. Therefore, a more integrated marketing communication strategy is required through the strengthening of destination branding, the optimization of digital media, and collaboration among stakeholders. These measures are expected to increase tourist visits and support the sustainable development of Gosong Telaga Beach as a leading tourist destination in Aceh Singkil Regency.